Electronic Attendance and Answer Script Submission Record System for Final Exam using RFID - Hamidon, Muhammad Faiz; Jabbar , Mohamad Hairol (Evolution in Electrical and Electronic Engineering, 2024)
The Electronic Attendance and Answer Script Submission Record System for Final Exams using RFID addresses the challenges of manual attendance tracking and exam script submission at Universiti Tun Hussein Onn Malaysia (UTHM). The system utilizes an RFID RC522 reader and ESP32 microcontroller to automate attendance and script tracking, with students using RFID-equipped matric cards. Data is processed in real-time, updating a MySQL database and displaying information on an LCD for monitoring. The results demonstrate significant time and labor savings compared to manual methods. For example, the system reduced the need for invigilators and shortened the time required for both attendance and script submission. These improvements enhanced the efficiency and accuracy of exam administration, with the system reliably recording attendance and verifying submissions. Future enhancements could include data analytics and biometric authentication for added security and insights.